The Effectiveness in Education Administration in Phrapariyattidhamma, Dhamma Division - อคฺควโร พระครูเมตตามงคลวิศิษฐ์; ฉิ่นไพศาล นิทรา (Journal of Educational Review Faculty of Education in MCU, 2018)
The education administration in Phrapariyatti dhamma, Dhamma Division of the Thai Sangha to be effective and successful depends on cooperation, support and understand of the members in the organization. The factors that should be improved are work quality, workload, work hour, work method and expenditure. With the improvement of these conditions, the work in Phrapariyattidhamma, Dhamma Division can fulfill the propagation of Buddhism and the Sangha affairs.